The Effect of Good Corporate Governance and Company Characteristic on Sustainability Report - Amanda Ika Permatasari; Heri Yanto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this study was to analyze the effect of good corporate governance and company charactheristics on sustainability report. The population of this study was 71 companies obtained from all consumer goods industry listed on the Indonesian Stock Exchange. The research sample was selected using purposive sampling technique and 12 companies was selected in order to obtain 48 units of analysis. This study used logistic regression analysis. The result of this study is that the audit committee has a positive effect on the sustainability report. Company size has a negative effect on sustainability report. Independent commissioner, managerial ownership, profitability, and liquidity have no effect on the sustainability report. Further research is expected to use different research objects, a wider research period, and use other variables outside of the variablles in order to see the effect of other variables on the sustainability report.